2014
DOI: 10.1007/s40261-014-0235-9
|View full text |Cite
|
Sign up to set email alerts
|

Management of Cognitive Determinants in Senile Dementia of Alzheimer’s Type: Therapeutic Potential of a Novel Polyherbal Drug Product

Abstract: The results of this study demonstrate the therapeutic potential of this novel polyherbal formulation for the management and treatment of SDAT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(64 citation statements)
references
References 40 publications
1
62
0
Order By: Relevance
“…Treatment durations were 6 to 64 weeks. Two studies were conducted in Iran, one in India, and the remainder in China (Table ). In 29 studies, the control was donepezil.…”
Section: Resultsmentioning
confidence: 99%
“…Treatment durations were 6 to 64 weeks. Two studies were conducted in Iran, one in India, and the remainder in China (Table ). In 29 studies, the control was donepezil.…”
Section: Resultsmentioning
confidence: 99%
“…45 Several preclinical analysis and clinical trials have proven the efficacy of these plants in management of cognitive deficits in aged population. 16,43,[46][47][48][49][50] Subsequently, metformin in addition to its antidiabtic properties has been also recently recognized as a potential treatment for neurodegenerative disorders such as AD. Studies have shown that metformin prevents apoptotic cascade in endothelial cell type by inhibiting Permeability Transition Pore (PTP) and blocking the release of cytochrome-c that will lead to cell death.…”
Section: Discussionmentioning
confidence: 99%
“…The polyherbal formulation has demonstrated a potential role in treatment and prevention of neurodegenerative disorders in the elderly by significantly improving cognitive and neuropsychiatric measures, reducing oxidative stress and neuroinflammation. 16 Whereas, metformin is the first line pharmacologic treatment for T2DM, as it decreases hepatic glucose production and improves insulin sensitivity by augmenting glucose uptake in the peripheral tissues, mainly muscles. 17,18 Metformin's efficacy, security profile, beneficial cardiovascular and metabolic effects and its ability to be associated with other antidiabetic or neuroprotective agents provided the basis to use the combination therapy in the present study.…”
Section: 13mentioning
confidence: 99%
See 2 more Smart Citations